Impact of sitting position on the formation of spinal curvatures in the sagittal plane of taxi drivers - preliminary report - Turon-Skrzypinska, Agnieszka; Tomska, Natalia; Ptak, Magdalena; Mosiejczuk, Hanna; Ciosek, Żaneta; Pelczar, Małgorzata; Rotter, Iwona (Journal of Education, Health and Sport, 2018)
Introduction: Human body posture is an individual feature influenced by environmental conditions and the type of performed work. The curvatures change with age, quality and style of life. Civilizational development has led to a sedentary lifestyle, which has an influence on postural defects formation. The aim of this study was to verify the effect of length of time for taxi drivers on spine curvature formation compared to people who adopt a sitting position. Materials and methods: The study comprised 60 subjects: 30 controls and 30 study subjects (taxi drivers), all with work history longer than 10 years. Triplicate measurements of spinal curvatures were taken using the Rippstein Plurimeter in a relaxed position, and results were saved according to the SFTR system. In addition, body height and weight were measured to calculate body mass index (BMI). Results: The average work time in the examined group was 57.7 and the control group 6.8 hours per week. The mean values of thoracic kyphosis and lumbar lordosis in the examined group were 36.3 and 17.9 degrees, respectively, versus 30.3 and 20.8 in the control group. Age and length of service had an impact on the shaping of the spinal curvatures. Greater value of BMI was associated with deeper thoracic kyphosis, but not with shallower lumbar lordosis. Conclusions: Adverse changes in shaping spinal curvatures progress with increasing age and length of the employment performed in the sitting position. Body mass index and body weight above the normal level contribute to deepening thoracic kyphosis.